1998
DOI: 10.1086/301998
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Background of Congenital Chloride Diarrhea in High-Incidence Populations: Finland, Poland, and Saudi Arabia and Kuwait

Abstract: Congenital chloride diarrhea (CLD) is an inherited intestinal disorder caused by mutations in the down-regulated in adenoma gene. In Finland, the disease is prevalent because of a founder effect, and all but one of the CLD-associated chromosomes carry the same mutation, V317del. In Poland, another area with a high incidence of CLD, as many as seven different mutations have been detected so far. A third known cluster of CLD, around the Persian Gulf, has not been genetically studied. We studied the allelic diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 23 publications
2
85
0
2
Order By: Relevance
“…These data suggest that the ⌬Y526/7 mutation is extremely sensitive to its cellular environment and is possibly a less severe mutation than the I544N, I675/6ins or G702Tins mutations. It should be noted that the ⌬Y526/7 mutant was identified in a patient who had the severe I675/6ins mutation on the other SLC26A3 allele (69).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the ⌬Y526/7 mutation is extremely sensitive to its cellular environment and is possibly a less severe mutation than the I544N, I675/6ins or G702Tins mutations. It should be noted that the ⌬Y526/7 mutant was identified in a patient who had the severe I675/6ins mutation on the other SLC26A3 allele (69).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear, however, whether sulfate transport is the major physiological function of DRA. Studies of humans with congenital chloride diarrhea (CLD), for which there is strong evidence of a defect in Cl Ϫ /HCO 3 Ϫ exchange in the ileum and colon (7)(8)(9), revealed that the disease was caused by null mutations in the DRA gene (10,11). This suggests that DRA might be a major transporter involved in Cl Ϫ absorption in the colon.…”
mentioning
confidence: 99%
“…Chronic dehydration and renal impairment is a known complication of CCD (7,8). However, chronic dehydration can cause low fecal chloride concentration (reaching <40 mmol/L) (2) necessitating repeated fecal examinations.…”
Section: Discussionmentioning
confidence: 99%